Mental Health among Children and Young Adults with Visual Impairments: A Systematic Review. (September 2017) - Augestad, Liv Berit
Introduction: The purpose of this study was to summarize current scientific knowledge relating to the occurrence of mood disorders among children with visual impairments. Methods: A systematic review was conducted of articles published between January 1998 and July 2016, inclusive. A total of 17 publications met the inclusion criteria, of which 15 reported studies with a cross-sectional design. The 17 publications represent 13 countries. Results: The majority of the studies suggested that children and young adults with visual impairments had more emotional problems than did their sighted peers. In addition, girls with visual impairments more often experienced serious symptoms of depression and anxiety than did boys with visual impairments, a finding that was in line with results for the general population. Two studies with a longitudinal design suggested that emotional problems among children and young adults with visual impairments might lessen over time. Discussion: Due to the different research purposes, study designs, definitions of visual impairment, participants' age ranges, cultures, countries, small sample sizes, measurements, and analyses of mental health, the overall results of the reviewed studies were inconsistent. To give children the best opportunities for good mental health, there is a need for more knowledge and for further longitudinal and randomized studies of high quality. Implications for practitioners: Social support, friendship, and independence in mobility seem to be important for enhancing the mental health of all children. Children with earlier onset and more severe visual impairments may be less likely to experience a reduction in their mental health problems over time.